2006
DOI: 10.1103/physrevlett.96.085701
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Steady States in Sheared Binary Fluids

Abstract: We simulate by lattice Boltzmann the steady shearing of a binary fluid mixture undergoing phase separation with full hydrodynamics in two dimensions. Contrary to some theoretical scenarios, a dynamical steady state is attained with finite domain lengths Lx,y in the directions (x, y) of velocity and velocity gradient. Apparent scaling exponents are estimated as Lx ∼γ −2/3 and Ly ∼γ −3/4 . We discuss the relative roles of diffusivity and hydrodynamics in attaining steady state.PACS numbers: 47.11.+jSystems that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
95
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(109 citation statements)
references
References 30 publications
(52 reference statements)
12
95
1
Order By: Relevance
“…(We define the mean velocity as u x =γy so that x, y, z are velocity, velocity gradient and vorticity directions respectively;γ is the shear rate. )Our recent simulations, building on earlier work of others [4,5], have shown that in two dimensions (2D), a NESS is indeed achieved [6]. In 3D, the situation is more subtle.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…(We define the mean velocity as u x =γy so that x, y, z are velocity, velocity gradient and vorticity directions respectively;γ is the shear rate. )Our recent simulations, building on earlier work of others [4,5], have shown that in two dimensions (2D), a NESS is indeed achieved [6]. In 3D, the situation is more subtle.…”
supporting
confidence: 55%
“…Even given the excellent parallel scaling of LB on multiprocessor machines, each one of these 12 datasets required more computational resource than the entirety of Ref. [6]. The production runs reported here were performed using 1024 processors of the IBM Blue Gene/L machine at the University of Edinburgh.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are in agreement with Ginzburg-Landau and Langevin calculations [7,8] as well as two-dimensional lattice-Boltzmann simulations of binary immiscible fluid mixtures as presented in [13,34,38]. However, to the best of our knowledge, there are no detailed theoretical studies of the dependence of domain growth properties on the surfactant concentration.…”
Section: Resultssupporting
confidence: 90%